2017
DOI: 10.1016/j.acvd.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Radial versus femoral access for coronary angiography and intervention is associated with lower patient radiation exposure in high-radial-volume centres: Insights from the RAY’ACT-1 study

Abstract: In this multicentre study, radial access was associated with lower radiation doses to patient than femoral access in high-radial-volume centres. Provided that radioprotection methods are implemented, radial access could be associated with lower patient radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…The RADIAL-CABG study compared transradial and transfemoral approaches in patients with a history of CABG and found longer procedural times and greater use of contrast agents with transradial procedures (13). This finding was supported by other trials and meta-analyses, as the radial approach has a steep learning curve and is technically more challenging, and is therefore associated with greater radiation exposure and use of contrast agents (14,15). Disadvantages of the radial approach, such as increased procedure time and contrast agent use, can be reduced by selection of a staged PCI strategy instead of ad hoc PCI in light of the present study.…”
Section: Discussionmentioning
confidence: 85%
“…The RADIAL-CABG study compared transradial and transfemoral approaches in patients with a history of CABG and found longer procedural times and greater use of contrast agents with transradial procedures (13). This finding was supported by other trials and meta-analyses, as the radial approach has a steep learning curve and is technically more challenging, and is therefore associated with greater radiation exposure and use of contrast agents (14,15). Disadvantages of the radial approach, such as increased procedure time and contrast agent use, can be reduced by selection of a staged PCI strategy instead of ad hoc PCI in light of the present study.…”
Section: Discussionmentioning
confidence: 85%
“…Among the most significant advantages of radial compared to femoral access are the need for shorter hospitalization and fewer adverse effects (39). Though the present survey did not take into account patients' satisfaction and cost-effectiveness of radial angiography, these two variables have been investigated in many other studies, showing radial access superior to femoral access (20,(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, Sciahbasi et al (20) concluded that radial approach was associated with higher operator and patient radiation exposure when performed by expert operators in patients with ACSs. In contrast, Georges et al (18, 19) stated that PCI via radial approach was associated with lower radiation exposure compared to femoral approach in high-radial-volume centers. They emphasized the importance of experience with regard to trans-radial angiography.…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis by Plourde et al (17) also demonstrated an increased radiation exposure in the diagnostic CA arm of the study (17). On the other hand, Georges et al (18, 19) have stated that radial approach during diagnostic CA was associated with lower radiation exposure than femoral approach in high-radial-volume centers. A possible explanation for the similar radiation exposure observed in the diagnostic CA arm of this study (as compared to other studies that demonstrated a higher radiation exposure during diagnostic CA) is that a radial TIG catheter was used, instead of standard Judkins left-and-right catheters.…”
Section: Discussionmentioning
confidence: 99%